2019
DOI: 10.1111/vsu.13311
|View full text |Cite
|
Sign up to set email alerts
|

Resection of urachal anomalies in dogs with recurrent lower urinary tract disease

Abstract: ObjectiveTo determine whether surgical removal of urachal anomalies improves the outcomes of dogs with recurrent lower urinary tract disease (LUTD) and bacterial urinary tract infection (BUTI).Study designRetrospective study.AnimalsThirty‐three dogs with urachal anomalies and recurrent LUTD or BUTI.MethodsMedical records of dogs with LUTD or BUTI and a diagnosis of urachal anomaly treated by partial cystectomy were reviewed. A minimum follow‐up of 9 months was required for inclusion.ResultsMedian age at onset … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…Some studies also reported that macroscopic diverticula may develop from microscopic diverticula, with the concomitant presence of disorders of the lower urinary tract, such as bacterial infections, urolithiasis, urethral plugs, sediment, or idiopathic cystitis. However, the exact relationship between vesicourachal diverticula and other disorders of the lower urinary tract is still unknown [ 4 , 27 , 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies also reported that macroscopic diverticula may develop from microscopic diverticula, with the concomitant presence of disorders of the lower urinary tract, such as bacterial infections, urolithiasis, urethral plugs, sediment, or idiopathic cystitis. However, the exact relationship between vesicourachal diverticula and other disorders of the lower urinary tract is still unknown [ 4 , 27 , 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dogs with lower urinary tract disease are often associated predisposing factors like anatomic anomalies, neoplasia, polyps, uroliths, pyelonephritis, prostatitis, ureterocele and urachus remnant, endocrine diseases, and immunosuppression (Visser et al, 2020). Bladder tumours represent 2% of cancer in dogs, and 90% of those tumours are malignant tumours and epithelial tumours.…”
Section: Introductionmentioning
confidence: 99%